2022
DOI: 10.1186/s13023-022-02541-0
|View full text |Cite
|
Sign up to set email alerts
|

HINT1 neuropathy in Lithuania: clinical, genetic, and functional profiling

Abstract: Background Recessive loss-of-function variations in HINT1 cause a peculiar subtype of Charcot-Marie-Tooth disease: neuromyotonia and axonal neuropathy (NMAN; OMIM[#137200]). With 25 causal variants identified worldwide, HINT1 mutations are among the most common causes of recessive neuropathy. The majority of patients are compound heterozygous or homozygous for a Slavic founder variant (c.110G>C, p.Arg37Pro) that has spread throughout Eurasia and America. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…3 ). This was further justified by previous reports showing that protein stability can differ between the two cellular systems 31,33 . The stability studies in both HeLa and yeast cells showed that p.Arg37Pro, p.Cys38Arg, p.His51Arg, and p.Val97Met were highly unstable ( Fig.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…3 ). This was further justified by previous reports showing that protein stability can differ between the two cellular systems 31,33 . The stability studies in both HeLa and yeast cells showed that p.Arg37Pro, p.Cys38Arg, p.His51Arg, and p.Val97Met were highly unstable ( Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Most of them have been identified in single families or isolated patients and often in compound heterozygous states with limited functional evidence of pathogenicity. Overall, there is in vivo data for only one-fourth of all HINT1 pathogenic variants 1,31,33 , while the impact of the rest of the variants has only been partially assessed in vitro 6,7 . Obtaining biological samples from the patients is not always possible, highlighting the need for standardized assays to test pathogenicity.…”
Section: Discussionmentioning
confidence: 99%